개인갈등이 학습활동에 미치는 영향: 정보획득과 아부의 조절효과를 중심으로 - 전학철(Xuezhe Quan); 강혜선(Hyesun Kang); 구자숙(Jasook Koo) (대한경영학회지, 2019)
현재 급변하고 있는 환경은 조직 내부의 종업원들이 새로운 지식의 학습에 대한 요구가 높아지고 있으며특히 종업원들 간의 소통을 통한 학습이 중요해지고 있다. 하지만 종업원들 사이의 갈등은 이와 같은 학습활동을 저애하고 있다. 갈등은 조직에 흔히 존재하며 학계에서도 그동안 많은 연구들을 해왔지만 기존 연구들에서는갈등의 팀 레벨에서의 연구를 많이 했었지, 개인 레벨에서 사람의 심리적 측면에 대한 연구는 상대적으로많지 않았다. 또한 업무갈등과 관계갈등의 상관관계가 높기 때문에 최근 연구에서는 차별화가 어렵다는 결과도보고되고 있다. 본 연구는 개인갈등(업무갈등, 관계갈등)과 학습활동 간의 관계를 밝히고 업무갈등과 관계갈등이 학습활동에 대한 영향이 부동한 심리적 과정을 통해 이루어짐을 밝히고자 하는 목적으로 수행되었다. 이에 더하여갈등을 대하는 개인의 태도가 다름에 따라 학습활동에 주는 영향의 크기도 다를 것으로 판단하고, 업무갈등이학습활동에 대한 영향을 조절할 것으로 예측되는 조절변수 정보획득과 관계갈등이 학습활동에 대한 영향을조절할 것으로 예측되는 조절변수 아부에 대한 조절 효과도 검증하려고 한다. 이를 위한 자료는 중국 다양한기업의 근로자 278명으로부터 수집하였다. 연구결과를 정리하면 다음과 같다. 먼저 업무갈등은 학습활동에 부정적인 영향을 나타냈고 정보획득은업무갈등이 학습활동에 미치는 부정적인 영향을 완화하는 것으로 나타났다. 다음 관계갈등도 학습활동에 부정적인 영향을 나타냈고 아부는 관계갈등이 학습활동에 미치는 부정적인 영향을 완화하는 것으로 나타났다. 마지막 추가 검증을 통해 정보획득이 관계갈등과 학습활동 간 관계에 미치는 조절효과와 아부가 업무갈등과학습활동 간 관계에 미치는 조절효과는 모두 유의하지 않게 나타났다. 따라서 업무갈등과 관계갈등이 학습활동에 대한 영향은 서로 차별화 되었다. 결론과 논의에서는 이와 같은 결과를 토대로 이론적 기여와 실무적 기여, 시사점과 한계 및 향후 연구 과제를 제시하였다. Employees need to learn new knowledge for changing environment. And communication with other employees is important to learn new knowledge about task. However, conflict between employees attenuate learning activities. Moreover, the existing conflict researchers have focused more on team level aspect than individual level aspect. Conflict emerges from individual level psychological processes, because teams do not think and feel, individuals do. This mean individual level conflict is core factor that attenuate learning activities. In addition, individual conflict include task conflict and relationship conflict. This two types of individual conflict may emerges different psychological processes that affect learning activities. However, there is a lack of research in this area. This article examines the relationship between individual conflict(task conflict, relationship conflict) and learning behavior. In addition, according to different attitudes of individuals to conflict, the magnitude of the impact on learning activities will be different. Consequently, we investigated the effects of information acquisition and ingratiation as moderating variables on learning behavior. Data used for empirical analysis was collected from 278 employees across Chinese companies. Results showed that task conflict was negatively related to learning behavior, the moderating effects of information acquisition on task conflict and learning behavior are statistically significant. The higher information acquisition level will attenuate the negative effect between task conflict and learning behavior. Results also indicated that relationship conflict was negatively related to learning behavior, the moderating effects of ingratiation on relationship conflict and learning behavior are statistically significant. The higher ingratiation level will attenuate the negative effect between relationship conflict and learning behavior. Moreover, the moderating effects of information acquisition on relationship conflict and learning behavior and the moderating effect of ingratiation on task conflict and learning behavior are not statistically significant. This mean that task conflict and relationship conflict processes are different. The implications, limitations and directions for future research are discussed. KCI Citation Count: 0